2020
DOI: 10.33235/wpr.28.1.8-16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the oral administration of silver nanoparticles on wound healing in male rats

Abstract: For referencing Samiee-Rad F et al. Effects of the oral administration of silver nanoparticles on wound healing in male rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The sections were blindly interpreted by an expert pathologist for the presence of angiogenesis and inflammatory cells (neutrophils, eosinophils, and mast cells), and fibroblasts using Iwf-Iox-Holland ocular lens. [ 8 ] Toluidine blue staining was also conducted for detecting mast cells.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sections were blindly interpreted by an expert pathologist for the presence of angiogenesis and inflammatory cells (neutrophils, eosinophils, and mast cells), and fibroblasts using Iwf-Iox-Holland ocular lens. [ 8 ] Toluidine blue staining was also conducted for detecting mast cells.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…Nowadays, tissue engineering, growth factors therapy, nanobiotechnologic and biologic-based treatments have been widely introduced to accelerate the WH process. [ 5 6 7 8 9 10 ] However, these new therapeutic approaches are very expensive and limited. For a long time, humans have found that the plants, soil, and their derivatives are effective in WH.…”
Section: Introductionmentioning
confidence: 99%